BMP-7 attenuates left ventricular remodelling under pressure overload and facilitates reverse remodelling and functional recovery. Issue 3 (11th April 2016) - Merino, David; Villar, Ana V.; García, Raquel; Tramullas, Mónica; Ruiz, Luis; Ribas, Catalina; Cabezudo, Sofía; Nistal, Juan Francisco; Hurlé, María A.
Abstract: Aims: TGF-β regulates tissue fibrosis: TGF-β promotes fibrosis, whereas bone morphogenetic protein (BMP)-7 is antifibrotic. To demonstrate that (i) left ventricular (LV) remodelling after pressure overload is associated with disequilibrium in the signalling mediated by these cytokines, and (ii) BMP-7 exerts beneficial effects on LV remodelling and reverse remodelling. Methods and results: We studied patients with aortic stenosis (AS) and mice subjected to transverse aortic constriction (TAC) and TAC release (de-TAC). LV morphology and function were assessed by echocardiography. LV biopsies were analysed by qPCR, immunoblotting, and histology. Pressure overload reduced BMP-7 and pSmad1/5/8 and increased TGF-β and pSmad2/3 in AS patients and TAC mice. BMP-7 correlated inversely with collagen, fibronectin, and β-MHC expressions, and with hypertrophy and diastolic dysfunction, and directly with the systolic function. Multiple linear regression disclosed BMP-7 and TGF-β as hypertrophy predictors, negative and positive, respectively. BMP-7 prevented TGF-β-elicited hypertrophic program in cardiomyocytes, and Col1A1 promoter activity in NIH-3T3 fibroblasts. The treatment of TAC mice with rBMP-7 attenuated the development of structural damage and dysfunction, and halted ongoing remodelling. The reverse remodelling after pressure overload release was facilitated by rBMP-7, and hampered by disrupting BMP-7 function using a neutralizing antibody or genetic deletion. Conclusion: The disequilibrium between BMP-7 and TGF-β signals plays a relevant role in the LV remodelling response to haemodynamic stress in TAC mice and AS patients. Our observations may provide new important insights aimed at developing novel therapies designed to prevent, halt, or reverse LV pathological remodelling in pressure overload cardiomyopathy.